2014
DOI: 10.37828/em.2014.1.8
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong>ROLE OF DIFFERENT TRICHOME STYLE IN THE RESISTANCE OF <em>LYCOPERSICON HIRSUTUM</em></strong> <strong>GENOTYPES TO<em> TUTA ABSOLUTA </em>(MEYRICK)<em> </em>(LEPIDOPTERA: GELECHIIDAE)<em> </em></strong></p>

Abstract: The tomato leaf miner (TLM), Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), is one of the major pests that attacks commercial tomato. TLM is becoming resistant to many of the pesticides used in the tomato fields. A potential alternative method of control is host plant resistance, which may be mediated by glandular trichomes. We studied glandular and non-glandular trichomes potentially related to tomato resistance of nine tomato genotypes (Lycopersicon hirsutum Humb & Bonpl), extensively cultivated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…They generally lay their eggs on the underside of the apical leaves because of their low calcium content (Proffit et al ., 2011; Cherif et al ., 2013). The number of eggs they lay are negatively correlated with the presence of compounds such as α‐pinene, β‐pinene, myrcene and limonene (Yarou et al ., 2017), trichome style I on the leaves (Khederi et al ., 2014), heptadecane (Suinaga et al ., 1999), and zingiberene (Azevedo et al ., 2003; Lima et al ., 2015). The density and diversity of glandular and nonglandular trichomes may also impact oviposition site preferences (Khederi et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…They generally lay their eggs on the underside of the apical leaves because of their low calcium content (Proffit et al ., 2011; Cherif et al ., 2013). The number of eggs they lay are negatively correlated with the presence of compounds such as α‐pinene, β‐pinene, myrcene and limonene (Yarou et al ., 2017), trichome style I on the leaves (Khederi et al ., 2014), heptadecane (Suinaga et al ., 1999), and zingiberene (Azevedo et al ., 2003; Lima et al ., 2015). The density and diversity of glandular and nonglandular trichomes may also impact oviposition site preferences (Khederi et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In Lycopersicon hirsutum, the increase of glandular trichome density, especially the abundance of 2-TD, was linked with the reduction of the larval development rate and survival of T. absoluta (Leite et al, 1999a;Leite et al, 1999b;Leite et al, 2001). Khederi et al (2014) found that, under greenhouse conditions, the most infested tomato genotypes (Mobil and Cal J N3) displayed the lowest IV and VI trichome style ranks of leaf blade, vein and domatia (glandular trichomes). De Oliveira et al (2012) confirmed that genotypes with higher densities of glandular trichomes had higher resistance than the susceptible controls, with the strain BPX-367D-238-02 being particularly notable in its resistance.…”
Section: Host Plants and Tuta Absoluta Controlmentioning
confidence: 92%
“…However, many other studies showed differences among the tested cultivars (Table 2). Susceptible tomato cultivars tested under laboratory or field conditions were characterized by a high number of mined (with or without larvae) leaves, stems or fruits, as well as a better suitability for egg-laying (Oliveira et al, 2009;Cherif et al, 2013;Khederi et al, 2014;Darbain et al, 2016;Sohrabi et al, 2016a;Sohrabi et al, 2016b;Allache et al, 2017;Ghaderi et al, 2017). Tomato cultivar 'Bravo' is commonly classified as one of the most susceptible cultivars, and was shown to be a better host plant than cultivar 'Tex 317': the latter led to a longer development time and a lower emergence rate (Silva et al, 2015).…”
Section: Host Plants and Tuta Absoluta Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, the insecticide thiacloprid (Calypso 480 SC ® -Bayer crop science, Leverkusen, Germany) was the least compatible with the zoophytophagous predator Macrolophus pygmaeus Rambur (Heteroptera: Miridae) [23]. Also, plant resistance using a high trichome density mechanism was found to reduce T. absoluta population density in some tomato cultivars tested for resistance [24,25]. Furthermore, tomato cultivars with high levels of Zingiberene were found to confer resistance to T. absoluta [26].…”
Section: Introductionmentioning
confidence: 95%